2006
DOI: 10.1063/1.2201894
|View full text |Cite
|
Sign up to set email alerts
|

Diode laser-induced fluorescence measurements of metastable argon ions in a magnetized inductively coupled plasma

Abstract: Velocity distribution functions of metastable argon ions ͑3dЈ4 F 7/2 ͒ have been measured to obtain metastable ion density and temperature by the diode laser-induced fluorescence ͑LIF͒ technique in magnetized inductively coupled plasma as a function of pressure, rf power, and magnetic field strength. Calculated density from a rate equation agrees with the trends observed in the experimental data. From the calculation, the metastable ion density should be over 10 7 cm −3 to obtain a LIF signal. From a dc bias e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Because the IVDFs in bulk plasmas and ion-acceleration fields are crucial in various plasma technologies, the LIF method has been extensively used to obtain the IVDFs, and its capability has been confirmed based on comparison with measurement results yielded by RFEAs. [27][28][29] To investigate the behavior of rare-gas ions in lowtemperature plasmas in the steady state, the LIF method has been utilized to diagnose bulk plasmas, [30][31][32][33] pre-sheaths, [34][35][36][37][38] ion sheaths formed on floated, 39,40 and DC-biased electrodes, [41][42][43][44][45] and plumes of electric propulsion devices. [46][47][48][49][50][51][52] To understand the dynamic behaviors of ions in plasmas, time-resolved LIF systems have been developed and applied to diagnose spatiotemporal fluctuations in plasma thrusters, [53][54][55][56][57] the temporal evolution of discharge and afterglow phases in pulsed plasmas, 58,59 and ion sheaths formed on AC-biased electrodes.…”
Section: Articlementioning
confidence: 99%
“…Because the IVDFs in bulk plasmas and ion-acceleration fields are crucial in various plasma technologies, the LIF method has been extensively used to obtain the IVDFs, and its capability has been confirmed based on comparison with measurement results yielded by RFEAs. [27][28][29] To investigate the behavior of rare-gas ions in lowtemperature plasmas in the steady state, the LIF method has been utilized to diagnose bulk plasmas, [30][31][32][33] pre-sheaths, [34][35][36][37][38] ion sheaths formed on floated, 39,40 and DC-biased electrodes, [41][42][43][44][45] and plumes of electric propulsion devices. [46][47][48][49][50][51][52] To understand the dynamic behaviors of ions in plasmas, time-resolved LIF systems have been developed and applied to diagnose spatiotemporal fluctuations in plasma thrusters, [53][54][55][56][57] the temporal evolution of discharge and afterglow phases in pulsed plasmas, 58,59 and ion sheaths formed on AC-biased electrodes.…”
Section: Articlementioning
confidence: 99%
“…LIF measurements of IVDFs of a pulsed inductively coupled plasma with have been reported by Jacobs et al [165] with a two-dimensional flow pattern of the ion velocity above the substrate. Jun et al have also been measured metastable ion density and temperature by the diode LIF technique in magnetized inductively coupled plasma as a function of pressure, RF power, and magnetic field strength [166]. The 2D ion velocity distribution of inductively coupled RF plasma had been measured with optical tomography via LIF in the bulk plasma and in the presheath of a plate with LIF and optical tomography, Zimmerman at al found that ion temperature depends on RF frequency and is weakly dependent on pressure [167].…”
Section: Plasma Processingmentioning
confidence: 99%
“…In the context of low pressure plasmas for materials processing, the technique has been used to measure ion densities, drift velocities, and energy distribution functions in dc and rf sheaths. [28][29][30][31][32][33][34][38][39][40][41][42] The electric field inside an rf sheath has also been measured by using a two-step process called LIF-dip in which the field is calculated from the Stark shifted fluorescence from ions. 43,44 Our implementation of the LIF technique uses the 3d 02 G 9/2 -4p 07 F 7/2 transition in argon.…”
Section: Description Of the Lif Technique And Experimentsmentioning
confidence: 99%